Riding the wave: monetary responses to aid surges in low-income countries - Buffie, E; Adam, C; O'Connell, S; Pattillo, C (2006)
We focus on the management of highly persistent shocks to aid flows, including HIPC or MDG-related increases in net flows, in the presence of currency substitution by the domestic private sector. Such shocks have beneficent long-run effects, but when currency substitution is high they can produce dramatic macroeconomic management problems in the sort run. What is the appropriate mix of money and exchange rate targeting in such cases, and the role of temporary sterilization? We analyze these and related issues in an intertemporal optimizing model that allows a portion of aid to be devoted to reducing the government’s seigniorage requirement. Our results argue that a managed float, with little or no sterilization of increases on the monetary base, is the most attractive approach.